Ensemble distribution model of Muga Silkworm (Antheraea assamensis) and its primary host plant Soalu (Litsea monopetala) in defined climate space - Kuladip Sarma; Vivek Chetry; Amal Bawri; Keshob Jyoti Borah; Bulbuli Khanikor; Tarali Kalita; Banasri Mech; Malabika Kakati Saikia; Manas Das (Scientific Reports)
Abstract Muga silkworm is one of the most economically and culturally important insect found in northeastern region and has immense future potential for entrepreneurship development owing to its sericogenic nature. The distribution of Muga SilkWorm (MSW) in wild are extremely important determinant for rearing a disease resistant domesticated variety that can significantly improve the yield of the later in terms of silk production. This paper aims to explore the distribution of the wild MSW in northeastern part of India in connection with the distribution of its primary host plant viz., Litsea monopetala(LM) Soalu in wild. Species Distribution Models (SDMs) have been used to know the potential distribution of MSW in historical climate scenario and also the impact of future climate has been assessed using a two climate models (CMCC-ESM2 and HadGEM3) with two different scenarios (SSPs) for each model. The climate space was defined in two dimensional space using Principal Component Analysis (PCA) to simplify the models. Altogether two model algorithms were used to get the final ensemble model for both the MSW and the two primary host plants. The model performed for MSW was found to be good with average AUC value greater than 0.80. On the contrary, the model performed for Litsea monopetala was found to be excellent with average AUC value greater than 0.90. Similarly, the ensemble models performed using future climatic data under the CMCC-ESM2 and HadGEM3 models for MSW have shown AUC values within acceptable range (0.78-0.82), whereas, model of the host plant (LM) have shown AUC values in higher range i.e. within excellent model category (0.90-0.95). Thus, in this reduced climate dimension, the potential distribution of the MSW and LM have been compared among current and future climate scenarios of two different models and district wise distribution potential has been calculated. The overlapping potential habitat of the invasive plant MSW and its host plant LM in Northeast India, particularly Assam and Arunachal Pradesh, is projected to experience significant and critical changes under future climate conditions between 2040 and 2060. The present research identifies climate-driven habitat changes, which may impact host plant availability and, in turn, silkworm survival and silk production. The results also highlight the importance of climate-resilient sericulture policy, adaptive agriculture practices, and conservation strategies to maintain Muga silk production under changing environmental conditions.